Recent Strategies in Preparation of Cellulose Nanocrystals and Cellulose Nanofibrils Derived from Raw Cellulose Materials - Hongxiang Xie; Haishun Du; Xianghao Yang; Chuanling Si (International Journal of Polymer Science)
The recent strategies in preparation of cellulose nanocrystals (CNCs) and cellulose nanofibrils (CNFs) were described. CNCs and CNFs are two types of nanocelluloses (NCs), and they possess various superior properties, such as large specific surface area, high tensile strength and stiffness, low density, and low thermal expansion coefficient. Due to various applications in biomedical engineering, food, sensor, packaging, and so on, there are many studies conducted on CNCs and CNFs. In this review, various methods of preparation of CNCs and CNFs are summarized, including mechanical, chemical, and biological methods. The methods of pretreatment of cellulose are described in view of the benefits to fibrillation.